A Phthalocyanine with an Olefin at Its Center as PotentialG‐Quadruplex Ligand. Issue 43 (16th November 2022) - Petroselli, Manuel
Abstract: We report the synthesis of a polycyclic dicationic phthalocyanine through N ‐functionalization of the internal core with an olefin (C=C) and compared with its porphyrin analogues. Potential application of this new class of molecules as G‐quadruplex (G4)‐targeting ligand has been investigated by computational point of view, showing encouraging results with respect to the current benchmarks. Abstract : A phthalocyanine internally functionalized with an olefin (C=C) is here report for the first time. Application of this new family of compounds as potential G4‐targeting ligands has been theoretically investigated, unveiling encouraging advantages with respect to the current benchmarks and relative porphyrin analugues.